The hemodynamic effects of compliance, bulging, and curvature in a saphenous vein coronary artery bypass graft model - Pedroso, Pedro D.; Hershey, Bradley L.; Anayiotos, Andreas (My University, 2003)
The development of Intimal Hyperplasia (IH) in saphenous vein coronary artery bypass grafts (SV-CABG) is responsible for the short-term patency of these grafts. Previous studies of SV-CABG models were performed on rigid anastomotic vessels. However, the effects of compliance, bulging and curvature at the anastomosis on the general hemodynamic field, due to compliance and geometric mismatch between the vein and the artery have not been evaluated. We studied axial and transverse velocities by Laser Doppler Velocimetry on a compliant, in vitro, anatomical model of an end-to-side saphenous vein graft (SVG) to left anterior descending (LAD). The model incorporated a bulge at the sinus and curvature at the graft-host junction. Physiologic pressure and flow conditions pertaining to SV-CABG were applied. The presence of the bulge and curvature showed differences in the velocity profiles in comparison with previous rigid model studies. Dynamic separation zones were temporally augmented at the flow divider. The moving stagnation point at the floor of the host vessel was observed to move past the toe of the model during the accelerating portion of the cycle. These findings suggest that the presence of the bulge curvature and compliance may further favor conditions for the development of intimal hyperplasia (IH) at the floor of a CABG.
Keywords: Hemodynamics; Coronary artery bypass; Hyperplasia